A retrospective study of propofol requirements for induction of anaesthesia in paediatric and geriatric dogs and cats. - Zapridis, V; Varkoulis, K; Kirmanidou, G; Tzortzi, I; Kazakos, G; Savvas, I; Anagnostou, T (Journal of the Hellenic Veterinary Medical Society, 2026)
The aim of this study was to investigate if propofol requirements for induction of anaesthesia are lower in paediatric and geriatric dogs and cats than in adults. Based on 5-year retrospective data, 3,266 dogs’ and 606 cats’ anaesthetic records were included in the study. Animals induced with propofol were grouped according to premedication and age. A Kolmogorov-Smirnov test revealed non-parametric data, while a Kruskal-Wallis and a Mann-Whitney test were used for comparisons. Paediatric and geriatric animals required significantly different propofol doses compared to adults. Premedication type and indication for anaesthesia also influenced propofol dose requirements. According to our study neonatal and paediatric dogs and cats require a higher dose of propofol for induction of anaesthesia when compared to adults and geriatrics, while geriatric patients require a lower dose compared to other groups. This finding comes in contrast to suggestions in veterinary literature that paediatric patients require a lower dose of propofol compared to adult animals. When propofol is used as a sole agent for induction of anaesthesia, patient age can affect the total amount of drug used.